The Efficacy of N-acetylcysteine Against Renal Oxidative Stress After Extracorporeal Shock Wave Treatment: An Experimental Rat Model - Dursun Baba; Kamil Çam; Yusuf Şenoğlu; Alpaslan Yüksel; Havva Erdem; Ekrem Başaran (Journal of Urological Surgery, 2020)

(untitled)
Objective:To evaluate effects of renal extracorporeal shock wave lithotripsy (SWL) on plasma Oxidative Stress index (OSI) and to observe histopathological alterations in an experimental model. Secondly, protective role of N-acetylcysteine (NAC) was investigated.Materials and Methods:A total of 24 rats were randomly divided into 3 groups as control (group 1), SWL + saline (group 2), and SWL + NAC (group 3). Study groups were further divided into two subgroups as short-term and long-term. In groups 2 and 3, 2000 shock waves were applied. Intraperitoneal saline was administered in group 2, and intraperitoneal NAC was given to group 3. No treatment was administered to group 1. Blood samples and nephrectomy specimens were obtained for biochemical and histopathological examinations, respectively. OSI was calculated by measuring plasma total antioxidant status (TAS) and total oxidant status (TOS). Acute and chronic histopathological damage were evaluated by light microscopy.Results:SWL caused a remarkable increase in oxidative stress. Strikingly, TOS levels were significantly lower (p=0.027) and TAS levels were significantly higher (p=0.006) in rats with SWL + NAC (group 3). As a result, OSI was lower (p=0.013). This effect was particularly significant in the short-term subgroup. It was also concluded that tubular damage and interstitial inflammation were higher in the SWL group (p=0.022). These acute histological alterations were slighter in rats with NAC.Conclusion:The current study demonstrated that SWL can cause severe oxidative stress and acute renal damage by increasing free oxygen radical production. NAC was effective in decreasing SWL-induced oxidative stress and preventing certain histological alterations to some extent.